Respuesta :
first , to make it easier to factor divide by 2:-
2(x^2 - 8x + 16) = 0
2(x - 4)(x - 4) = x
x - 4 = 0 to x = 4 Answer
Because a quadratic equation has to have 2 solutions we say that x = 4 Duplicity 2.
2(x^2 - 8x + 16) = 0
2(x - 4)(x - 4) = x
x - 4 = 0 to x = 4 Answer
Because a quadratic equation has to have 2 solutions we say that x = 4 Duplicity 2.
Answer:
x= 4 x=-4
Step-by-step explanation:
In order to solve this we first have to factorize the equation, to make it solvable, as you can see all of the terms are multiples of 2 so we first factorize by dividin all of them by 2:
2x^2-16x+32=0
2(x^2-8x+32)=0
No we just factorize the perfect square trinomial that is left inside the parenthesis:
2(x-4)(x+4)=0
So the two solutions for x would be -4 and 4.